Visitors' satisfaction toward facilities provided at Taman Tasik Metropolitan Kepong, Kuala Lumpur - Ab Ghafar, Mohd Zulhanafi Shaffwan (2016)
Visitors’ to the Taman Tasik Metropolitan Kepong, Kuala Lumpur has a variety of purposes such as jogging, exercise, sightseeing and kite flying. The research is important for management to find out what visitors’ need in this park. The objective of this study is to determine visitors’ satisfaction towards facility provided at Taman Metropolitan Kepong, Kuala Lumpur. Other than that, this research also to determine visitors’ socio demographic background,visitation characteristics, and the relation of gender and marital status of visitor with their satisfaction level. Hundred and fifty respondent were interviewed at the site using structured questionnaire. The data has been collected from 19th January 2016 until 22nd February 2016. Frequency analysis was used to determine their visitation characteristics. The result shows that most visitors are unsatisfied with parking lot facility. In addition, also found satisfaction with all the facilities associated with gender, age and educational level of visitors.